Pendampingan Pembuatan Krim Penghangat Tubuh Dari Minyak Sereh Wangi Dan Biji Buah Pala Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - Siti Aisyah Tanjung; Ruseni; Masni; Abdal Kahfi; Iche Windari; Laili Mubarok; Nurfitrahtul Hasanah (STIKES Columbia Asia Medan, 2025)
Mothers in Bingkat Village have daily activities as housewives and participate with their husbands as farmers and raise livestock, as well as social activities of village organizations and religion, not to the point of increasing family economy. Making warming cream from natural ingredients, such as nutmeg, lemongrass, and torch ginger or other plants around the house is very easy, simple tools, low cost, and has economic value. The target of the activity is to provide assistance in making body warming cream and relieving aches and pains. Based on this, it is deemed necessary to provide assistance in making body warming cream and aches and pains. Assistance is not only in making, but also in good product packaging and counseling on marketing direction of products made by the people of Bingkat Village. This natural cream product has a selling value, so it is hoped that it can increase family income and welfare.